Peningkatan Kualitas Pembelajaran Kelas Pengantar Ekonomi Pembangunan Melalui Metode Case Base Learning (CBL) - Annur Fitri Hayati; Oknaryana Oknaryana; Jean Elikal Marna; Zetri Rahmat; Wiranti Tranitasari; Gusma Yeni (Jurnal Inovasi Pendidikan Ekonomi (JIPE), 2022)
Classroom Action Research (CAR) or Penelitian Tindakan Kelas (PTK) is research conducted by educators (lecturers) in class that focus on improving the learning process. Classroom Action Research functions as a tool for solving problems that arise in class and also as a tool for in-service training, where lecturers use new skills and methods and sharpen their analytical abilities. PTK is carried out through a cycle consisting of four stages, starting with planning, followed by action and observation activities, and ending with reflection to analyze the data obtained through action. The learning model used in this study is Case Based Learning, a case-based approach that engages students in discussions of specific situations and examples of real-world events. Based on research the Case Base Learning model can improve the quality of learning in class, this can be seen in the increase in learning outcomes, motivation, and student activity.